Polarization: Concepts, measurement, estimation - Jean-Yves Duclos; Joan Esteban; Debraj Ray (Luxembourg Income Study (LIS), 2002)
The purpose of this paper is two-fold. First, we develop the measurement theory of polarization for the case in which asset distributions can be described using density functions. Second, we provide sample estimators of population polarization indices that can be used to compare polarization across time or entities. Distribution-free statistical inference results are also derived in order to ensure that the orderings of polarization across entities are not simply due to sampling noise. An illustration of the use of these tools using data from 21 countries shows that polarization and inequality orderings can often differ in practice.
Keywords: 330; Einkommensverteilung; Disparitätsmaß; Theorie; Welt; Soziale Gruppe